Isolation and Identification of Wild Isolate of Newcastle Disease Virus from Broiler Farm in Diyala Province: Virological and Histopathological Study - Al-Azawy, Amer Khazaal; Sadun Al-Ajeeli, Karim; Ismail, Alaa (The Iraqi Journal of Veterinary Medicine, 2019)
A broiler poultry farm of six weeks old, vaccinated with LaSota Newcastle disease virus vaccine. The flock was infected with a virulent Newcastle disease virus with mortality rate up to 90%. Newcastle disease virus was isolated from infected birds in embryonated chicken eggs and identified by haemagglutination inhibition test using hyperimmune serum prepared against LaSota viral vaccine. Median Death Time, Intracerebral Pathogenicity Index and Intravenous Pathogenicity Index proved that the virus was a virulent viscerotropic isolate. In experimental infection, broilers were vaccinated twice with LaSota strain, the level of anti-Newcastle disease virus IgG was checked by Enzyme-linked immunosorbent assay test pre and post vaccination and the birds were challenged with the same isolated virulent isolate at 35 days old, the virus was inoculated by oral and nostril routs. The challenge virus produced the same sever clinical signs and the mortality rate reached up to 70%. Tissue samples were collected from intestine, kidneys, lung, trachea, spleen, liver, and the brain of the experimentally infected broilers, they showed sever pathological changes. It seems that vaccination with commercial available vaccine could not produce enough protection against virulent circulating Newcastle disease virus strains, accordingly preparation of viral vaccine from local virulent isolate is recommended after attenuation or inactivation.